The effects of supergrids and superblocks on the transformation of the historic urban fabric of Kashan city in Iran - Karbalaei Hassani Elham (Lodz University of Technology Press, 2023)
Building a broad network of wide and long routes in the center of ancient cities inspired the most significant modernization efforts in Iranian cities between 1925 and 1941. This method transformed the urban grid and destroyed historic urban areas; however, it helped transportation tremendously. A city's supergrid is a notion that is superimposed on an existing city structure, triggering a transformation process that results in a complete reorganization of the city's layout, as Moudon stated in 2019. Regular and semi-regular grid patterns and the superimposed modern supergrids have emerged as the dominating pattern of expansion, enclosing the ancient city's organic form inside the confined and transformed historic core. This research's primary methodology is based on the Italian approach of urban morphology, which is focused on the idea that a city's history is written within its built urban fabric. My investigation began by reading the most recent superimposed layers in contemporary time and progressing backward by deleting them in each phase of city formation until I reached the city's origins before the Islamic period. Kashan's morphological cadastral cartographies reveal the city's most recent footprints. The strategy has been implemented by cutting procedures, which superimposed new grids and levels on the medieval town's topography and architecture. The historical aggregate's architectural structure may still be observed inside the modern network. This study examines how the new supergrid axes have changed the behavior of the built fabric on both sides of the route margins.
Keywords: superblock; supergrid; urban morphology; Kashan City; historic urban context; superblok; supersieć; morfologia miasta; miasto Kashan; historyczny kontekst miejski